Diet diversity and pesticide risk mediate the negative effects of land use change on solitary bee offspring production. Issue 6 (7th April 2020) - Centrella, Mary; Russo, Laura; Moreno Ramírez, Natalia; Eitzer, Brian; van Dyke, Maria; Danforth, Bryan; Poveda, Katja
Abstract: Threats to bee pollinators such as land use change, high pesticide risk and reduced floral diet diversity are usually assessed independently, even though they often co‐occur to impact bees in agroecosystems. We established populations of the non‐native mason bee Osmia cornifrons at 17 NY apple orchards varying in proportion of surrounding agriculture and measured floral diet diversity and pesticide risk levels in the pollen provisions they produced. We used path analysis to test the direct and indirect effects of different habitats, diet diversity and pesticide risk on emergent female offspring number and weight. High proportions of agricultural habitat surrounding bee nests indirectly reduced the number of female offspring produced, by reducing floral diet diversity in pollen. When the proportion of agriculture surrounding bee nests was high, bees collected increased proportions of Rosaceae in their pollen provisions, which marginally (0.05 <  p  < 0.1) increased fungicide risk levels in pollen. This, in turn, marginally reduced female offspring weight. In contrast, female offspring weight increased as proportions surrounding open habitat (wildflowers, grassland and pasture) increased, but this effect was not influenced by proportion Rosaceae or fungicide risk levels in pollen. Synthesis and applications . Threats to bee health such as land use change, pesticide exposure and changes in pollen diet composition are often studied in isolation. However, our results suggest that these threats can simultaneously influence one another to impact bee populations in the agroecosystems where we rely on them for pollination. By replacing surrounding agricultural habitats with more natural habitats, such as grasslands and pastures, we can increase floral diet diversity and reduce pesticide exposure in bee‐collected pollen, resulting in healthier mason bee populations in apple orchards. Abstract : Threats to bee health such as land use change, pesticide exposure and changes in pollen diet composition are often studied in isolation. However, our results suggest that these threats can simultaneously influence one another to impact bee populations in the agroecosystems where we rely on them for pollination. By replacing surrounding agricultural habitats with more natural habitats, such as grasslands and pastures, we can increase floral diet diversity and reduce pesticide exposure in bee‐collected pollen, resulting in healthier mason bee populations in apple orchards.